O impacto das ações afirmativas no ensino superior e o desempenho dos alunos - Silva, Talita de Moraes Gonçalves (2014)
This article has estimated the group effects in the performance of students attending courses in undergraduate institutions that have implemented, voluntary or compulsory, policies of affirmative action in the student admission process. The results suggested a negative and modest impact on performance of the students exposed the implementation of these policies.